Fe/Sb2Te3 Interface Reconstruction through Mild Thermal Annealing. Issue 19 (23rd August 2020) - Longo, Emanuele; Wiemer, Claudia; Cecchini, Raimondo; Longo, Massimo; Lamperti, Alessio; Khanas, Anton; Zenkevich, Andrei; Cantoni, Matteo; Rinaldi, Christian; Fanciulli, Marco; Mantovan, Roberto
Abstract: When coupled with ferromagnetic layers (FM), topological insulators (TI) are expected to boost the charge‐to‐spin conversion efficiency across the FM/TI interface. In this context, a thorough control and optimization of the FM/TI interface quality are requested. Here, the evolution of the chemical, structural, and magnetic properties of the Fe/Sb2 Te3 heterostructure is presented as a function of a rapid mild thermal annealing conducted on the Sb2 Te3 ‐TI (up to 200 °C). While the bilayer is not subjected to any thermal treatment upon Fe deposition, the annealing of Sb2 Te3 markedly improves its crystalline quality, leading to an increase in the fraction of ferromagnetic Fe atoms at the buried Fe/Sb2 Te3 interface and a slight lowering of the magnetic coercivity of the Fe layer. The method is an efficient tool to clean up the Fe/Sb2 Te3 interface, which may be extended to different FM/TI heterostructures. Simultaneously to the interface reconstruction, a constant ≈20% fraction of FeTe develops at the interface. Since FeTe can display superconductivity, the Fe/Sb2 Te3 system could have potentialities for exploiting phenomena at the edge of magnetism, superconductivity and topology. Abstract : Topological insulators are in the focus for enhancing spin‐to‐charge conversions when in contact with ferromagnets, and to optimize the interface is demanding. A thermal annealing process of Sb2 Te3 is presented, which improves the chemical, structural, and magnetic properties of Fe/Sb2 Te3 heterostructure, even if Fe is not subjected to any thermal treatment. The method could be easily extended to similar systems.